Ecology of endangered damselfly Coenagrion ornatum in post-mining streams in relation to their restoration - Tichánek, Filip (Jihočeská univerzita, 2016)
The thesis explores various aspects of ecology of endangered damselfly Coenagrion ornatum, the specialists for lowland headwaters, in post-mining streams of Radovesicka spoil. The first part of thesis is manuscript which has been already submitted in Journal of Insect Conservation. In the first part, we focused on population estimate of the local population using capture-recapture method, and explored its habitat requirements across life stages and spatial scales. In the next part, I assess mobility of the focal species and reveals basic distribution patterns. Finally, the thesis suggest various implications for restoration of post-mining freshwaters and conservation of the studied species.
Ecology of endangered damselfly Coenagrion ornatum in post-mining streams in relation to their restoration
Keywords: drainage ditches; headwaters; insect conservation; Odonata; restoration ecology; secondary habitats